Anti-Cancer Effect of Neural Stem Cells Transfected with Carboxylesterase and sTRAIL Genes in Animals with Brain Lesions of Lung Cancer - Jung Hak Kim; Jae Sung Ahn; Dong-Seok Lee; Seok Ho Hong; Hong J. Lee (MDPI AG, 2023)
A metastatic brain tumor is the most common type of malignancy in the central nervous system, which is one of the leading causes of death in patients with lung cancer. The purpose of this study is to evaluate the efficacy of a novel treatment for metastatic brain tumors with lung cancer using neural stem cells (NSCs), which encode rabbit carboxylesterase (rCE) and the secretion form of tumor necrosis factor-related apoptosis-inducing ligand (sTRAIL). rCE and/or sTRAIL were transduced in immortalized human fetal NSCs, HB1.F3. The cytotoxic effects of the therapeutic cells on human lung cancer cells were evaluated in vitro with the ligands and decoy receptor expression for sTRAIL in the presence of CPT-11. Human NSCs encoding rCE (F3.CE and F3.CE.sTRAIL) significantly inhibited the growth of lung cancer cells in the presence of CPT-11 in vitro. Lung cancer cells were inoculated in immune-deficient mice, and therapeutic cells were transplanted systematically through intracardiac arterial injection and then treated with CPT-11. In resting state, DR4 expression in lung cancer cells and DcR1 in NSCs increased to 70% and 90% after CPT-11 addition, respectively. The volumes of the tumors in immune-deficient mice were reduced significantly in mice with F3.CE.sTRAIL transplantation and CPT-11 treatment. The survival was also significantly prolonged with treatment with F3.sTRAIL and F3.CE plus CPT-11 as well as F3.CE.sTRAIL plus CPT-11. NSCs transduced with rCE and sTRAIL genes showed a significant anti-cancer effect on brain metastatic lung cancer in vivo and in vitro, and the effect may be synergistic when rCE/CPT-11 and sTRAIL are combined. This stem-cell-based study using two therapeutic genes of different biological effects can be translatable to clinical application.